The impact of international treaties on the shape of national criminal law on the basis of Article 48 1 of the Istanbul Convention - Bek, Dominika; Sitarz, Olga (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The Council of Europe Convention on preventing and combating violence against women and domestic violence has been ratified by 29 countries, including Poland. Among other things, pursuant to art. 48, Parties shall take the necessary legislative or other measures to prohibit mandatory alternative dispute resolution processes, including mediation and conciliation, in relation to all forms of violence covered by the scope of this Convention. It is regulation that will provide a clear illustration of the reasons which render the implementation difficult or even impossible. Considerations set out in this paper will focus on three basic aspects — the ambiguity of the wording of art. 48 1, discrepancy between the legal text and its official substantiation, as well as the commanding and peremptory tone of its language.
Keywords: Konwencja Stambulska; wdrożenie; mediacja między ofiarą a sprawcą; adrenalina; przemoc w rodzinie; przemoc wobec kobiet